2000
DOI: 10.1094/phyto.2000.90.12.1300
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Spore Efficacy by Host Genetic Background in a Wheat Powdery Mildew Population

Abstract: A field experiment was designed to test the hypothesis of for increased reproductive ability on different host genetic backgrounds within a wheat powdery mildew population. Studies have suggested that, in host mixtures, such selection could increase the reproduction rate of simple patho-types that always develop on the same host genetic background, whereas complex pathotypes should not be affected because they infect different host genotypes. In our experiment, the Erysiphe graminis population reproduced for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
4
38
0
1
Order By: Relevance
“…This was consistent with the increase in disease intensity recorded in different fungal pathogens after only a few asexual cycles (29)(30)(31)(32). Isolates of the final population (Pf) showed greater sporulation intensity under winter conditions, and a shorter latency period under spring conditions, than isolates of the initial population (Pi).…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with the increase in disease intensity recorded in different fungal pathogens after only a few asexual cycles (29)(30)(31)(32). Isolates of the final population (Pf) showed greater sporulation intensity under winter conditions, and a shorter latency period under spring conditions, than isolates of the initial population (Pi).…”
Section: Discussionsupporting
confidence: 87%
“…This result contrasts with those obtained previously for other fungal plant pathogens. Villareal and Lannou (38) and Andrivon et al (2) showed that directional selection for increased aggressiveness takes place in Erysiphe graminis and Phytophthora infestans populations, respectively, during the epidemic stage. Some fungal plant pathogens alternate between highly aggressive life stages and life stages in which highly aggressive strains are selected against, whereas the aggressiveness of other fungal plant pathogens, such as Mycosphaerella graminicola (9) and E. necator, remains stable.…”
Section: Discussionmentioning
confidence: 99%
“…Pathotypes were sometimes compared for quantitative traits on the basis of a single isolate per pathotype (Katsuya and Green 1967). Quantitative variation in pathogenicity among individuals can be the consequence of a change from avirulence to virulence (Vera Cruz et al 2000), or related to the number of qualitative virulence factors (Thrall and Burdon 2003) but it is likely that aggressiveness variations also occur independently of qualitative virulence (Villaréal and Lannou 2000;Pilet et al 2005;Lannou 2012). From the available literature, this is however not easy to establish for pathogens with clonal population structures.…”
mentioning
confidence: 99%